2006
DOI: 10.1179/174328906x128234
|View full text |Cite
|
Sign up to set email alerts
|

On consolidation of self-reinforced polypropylene composites

Abstract: Self-reinforced polypropylene composites (SRPPC) were manufactured with film stacking method at different processing temperatures (T5150-175uC) at a constant pressure of 5 . 5 MPa and holding time of 90 s with a nominal reinforcement content of 50 wt-%. For reinforcement carded PP, for matrix random PP copolymer films with two different melt flow rate (MFR) values were used. Static tensile and dynamic falling weight impact tests were performed on the manufactured SRPPC sheets. To characterise the consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…For both structures, as expected, the tensile strength increases with increasing processing temperature and with increasing reinforcing fiber content. According to our earlier studies [4,11,12] the tensile parameters (strength, modulus) decreased at temperatures higher than 170°C owing to the relaxation and partial melting of the reinforcing fibers. So, in our present study we have focused on the processing temperature range of 160-170°C.…”
Section: Static and Dynamic Testsmentioning
confidence: 81%
See 2 more Smart Citations
“…For both structures, as expected, the tensile strength increases with increasing processing temperature and with increasing reinforcing fiber content. According to our earlier studies [4,11,12] the tensile parameters (strength, modulus) decreased at temperatures higher than 170°C owing to the relaxation and partial melting of the reinforcing fibers. So, in our present study we have focused on the processing temperature range of 160-170°C.…”
Section: Static and Dynamic Testsmentioning
confidence: 81%
“…(ii) Chopped (≈80 mm) matrix giving and as reinforcement working fibers were carded and needle punched together as described in details in Ref. [12] (hereafter referred to as: carded -it is shown on Figure 1). The identical textile layers (in case of knitted 8, in case of carded 4 plies) were placed on each other by keeping the reinforcement alignment constant; therefore the resulting composite plates are of anisotropic nature.…”
Section: Materials and Their Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to minimize the degradation, the hot compaction process should be performed as rapidly as possible. Bárány, Karger-Kocsis and coworkers [14][15][16]34] studied the processing parameters of self-reinforced PP composites and concluded that the consolidation temperature is more suited to control the parameter than the holding time when the consolidation pressure is invariable. The increase in the consolidation temperature caused an increase in tensile properties, but a decrease in the impact energy.…”
Section: Fabrication and Mechanical Properties Of Self-reinforced Polmentioning
confidence: 99%
“…Since the components of all-PP composites belong to the same polymer family, the TPE itself should also be based on PP. To compare the selected Versify type TPE with the Tipplen R959A-type (TVK, Tiszaújváros, Hungary) PP copolymer (which was used in our previous study [23]) FTIR tests were performed on Bruker Tensor 27 spectrophotometer on the matrix foil (50 µm thick) in a wave number range: 4000…400 cm -1 with resolution of 2 cm -1 .…”
Section: Introductionmentioning
confidence: 99%